Repeated small-volume exchange transfusion for hyperleukocytosis in pediatric acute leukemia: A retrospective analysis - Zhang, Dongxiu; Lin, Hailong; Huang, Leting (Frontiers in Pediatrics, 2023)
Leukapheresis is a procedure conducted to reduce hyperleukocytosis in children with acute leukemia. Although the use of this procedure is under debate, a repeated small-amount exchange transfusion along with leukapheresis received satisfactory results. Forty-seven patients (32 ALL and 15 AML) with acute leukemia were enrolled in the study between January 2017 and June 2022; they underwent repeated small amount exchange transfusion. The following were measured: indicators of demographic and clinical characteristics, time of procedure, PWBC count, hemoglobin, platelet count, blood biochemistry, electrolytes, coagulation, leukostasis, TLS, DIC, AE, and SAE. Indicators of demographic and clinical characteristics showed no statistical differences between ALL and AML patients, but differences were observed in PWBC counts (424.2 ± 135.6) and (223.8 ± 58.0) × 109/L. The procedures need 3 to 8 processes respectively and the average times showed no statistical difference between ALL and AML. PWBC count gradually reduced to <100 × 109/L; hemoglobin, platelet count, K+, Na+, and Ca2+ kept steady. ALT, AST, TBil, BUN, creatinine, troponin-I, CK-MB, PT, and APTT maintained normal levels or recovered from disorder levels. The manifestations of leukostasis, TLS, and DIC alleviated or even disappeared. No cases of AE and SAE occurred. The requirement of total blood volume is based on initial PWBC counts, manifestations of Leukostasis and age. Repeated small amount exchange transfusion is effective and safe for the treatment of hyperleukocytosis in children with acute leukemia.